español - De-la-Peña-Meniz, Walter Jerry (2020)
Objective: to acknowledge the pathological, clinical and epidemiological characteristics of early-onset severe preeclampsia and late-onset severe preeclampsia in patients admitted in the maternal intensive care unit (MICU) of the maternal perinatal national institute (INMP). Methods: We develop a comparative transversal descriptive study. Clinical charts were reviewed from August first of 2014 until September thirty of 2018 getting 332 charts of early-onset preeclampsia and 325 charts of the late-onset type. Results: The mean age of the patients with early-onset severe preeclampsia was 27.84 years (IC 26.88- 28.81) (p: 0.72), the mean for hospital stay was higher in the patients with the early-onset type (p: 0.006). The new born showed statistical difference in weight (p=0.000), height (p=0.000) and the APGAR score was lower in the early-onset group (p=0.000). We did not found difference statistically significative between early-onset severe preeclampsia and eclampsia (p=0.481). Conclusion: we did not found differences between early onset preeclampsia and eclampsia. New born had lower weight, height and APGAR score in the early-onset group than in the late-onset group.